Efficiency of Extended Temperature Schedules for Regulation of Heating Networks with Different Shares of Hot Water Supply Load - Suvorov D.M.; Tatarinova N.V. (Problems of the Regional Energetics, 2025)
The aim of this work is to study the efficiency of extended temperature schedules for regulating heat supply systems in a wide range of changes in the share of the HWS load. To achieve this aim, the following tasks were solved: initial and extended temperature schedules were calculated and con-structed; calculations of the operating modes of a model CHPP were performed and its energy effi-ciency indicators were determined for both the initial and extended temperature schedules; an analy-sis of the identified dependencies was performed both in a degree-by-degree representation and inte-grally for the entire heating period. The most significant results of the work are the following: for all variants of the calculated parameters, the specific electricity generation with extended schedules is higher than with the initial ones; for any share of the HWS load, the use of extended regulation schedules reduces the specific consumption of equivalent fuel for electricity supply by approximately 1% compared to the initial schedules; the best result for any share of the DHS load is the use of a reduced temperature schedule with a design temperature of delivery water of 110℃. The calculations carried out confirm that for any share of the DHS load, the transition to extended temperature schedules ensures a significant increase in the efficiency of the heat supply system. The significance of the results of the work lies in their applicability for setting and solving problems of ensuring max-imum energy efficiency of heat supply systems based on CHPPs.